PHASE TRANSFORMATIONS DURING CRYSTALLIZATION OF A SOLID SOLUTION OF STRONTIUM-SUBSTITUTED DOUBLE PEROVSKITE - A. L. Gurskii; N. A. Kalanda; M. V. Yarmolich; I. A. Bobrikov; S. V. Sumnikov; A. V. Petrov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The kinetics of phase contents modification in the process of SrBaFeMoO6–δ crystallization from a stoichiometric mixture of SrCO3 + BaCO3 + 0,5Fe2O3 + MoO3 simple oxides using the solid phase method has been investigated. In the temperature region of 300–1200°С, a number of endotermic effects have been detected. Herewith, the first one (with maximum around 552°С) and the third one (with maximum around 743°С) are accompanying by the significant decrease of the mass of specimen. In the temperature range of 946–1200°С, the mass change of specimen is practically not observable, while the thermal effect is still present, and the specimen remains not single-phase one. This indicates the difficulty of the flow of solid phase reactions with the formation of solid solution of barium-strontium ferromolybdate. During analysis of the change of the phase composition consisting of a mixture of initial reagents of stoichiometric relation SrCO3 + BaCO3 + 0,5Fe2O3 + MoO3, it has been observed that with increasing temperature, complex compounds BaMoO4, SrFeO3 appear almost simultaneously, then SrBaFeMoO6–δ appears consequently. Thus, the compounds BaMoO4 и SrFeO3, are structure forming for the solid solution of barium-strontium ferromolybdate. With further temperature increase up to 770°С the formation of new compound ВаFeO3 with disappearing SrFeO3 was detected. In this case, the amount of double perovskite increases faster than that of barium molybdate. The main accompanying compounds at the crystallization of the SrBaFeMoO6–δ double perovskite solid solution are BaMoO4 and SrFeO3. It was established that at the initial stage of the interaction, the resulting solid solution of barium-strontium ferromolybdate is enriched with iron and its composition changes during the reaction in the direction of an increase of the molybdenum content, as in the case of other precursor combinations.